Formulation of Silver Nanoparticle Mouthwash and Testing of Antibacterial Activity Against Staphylococcus aureus - Rahmi Annisa; Begum Fauziyah; Dewi Sinta Megawati; Firdausi Zahrah (Journal of Tropical Pharmacy and Chemistry, 2023)
Silver Nanoparticles (AgNP) are silver particles of no more than 100 nm in size. Silver nanoparticles have antimicrobial characteristics and have been applied to various fields as antibacterial agents. This study aims to formulate and examine the antibacterial activity in preparing silver nanoparticle mouthwash on Staphylococcus aureus. The silver nanoparticles are synthesized using a chemical reduction method, of which the wavelength is then characterized using UV-Vis spectrophotometry, and the PSA instrument is used for particle size. Silver nanoparticles are formulated for a mouthwash with various concentrations such as 0%, 60%, 70%, and 80% consecutively as formula 1, 2, 3, and 4. The observation is then performed on the organoleptic, pH, stability, and bacterial activity of the Staphylococcus aureus using the disk diffusion method. The study results indicate that the preparation of silver nanoparticle mouthwash has a good organoleptic; the average pH of formula 1, 2, 3, and 4 consecutively is 3.40, 3.40, 3.46, and 3.54; however, it is not stable during the storage stage. The result of the antibacterial activity test on Staphylococcus aureus bacteria shows that formula 2 has the most oversized average inhibition zone diameter that is 13.14±0.31 mm compared to formulas 1, 3, and 4, namely 5.20±0.44; 12.40±0.74; and 8.40±0.89 mm. The active formula of mouthwash preparation to inhibit the growth of Staphylococcus aureus bacteria is formula 2.